Extent and Rate of Deforestation and Forest Degradation (1986–2016) in West Bugwe Central Forest Reserve, Uganda - Fatuma Mutesi; John Robert Stephen Tabuti; David Mfitumukiza (International Journal of Forestry Research)
Understanding the extent of land cover change and the forces behind land cover changes is essential in designing appropriate restoration strategies. Land cover changes at local scales or the factors that lead to cover change have not been documented for much of Uganda. We undertook this study in West Bugwe Central Forest Reserve (WBCFR) to fill this gap. We used remote sensing to determine land cover changes for a 30-year period, 1986–2016, and an interview survey to investigate the drivers of these changes. Our results show that the forest in this reserve has declined extensively by over 82% from 1,682 ha to 311 ha corresponding to an average change of −1.18% per year. The wetland has also been extensively degraded. Both the forest and wetland have transitioned into shrub land. The key drivers that have been highlighted by the survey are poverty (86%), population growth (56%), and associated harvesting of woody products (86%) for subsistence and income generation. We conclude that the forest in WBCFR has been extensively and rapidly deforested and degraded by humans.